What determines the relocation tendency of manufacturing firms? - Elif Alkay (European Regional Science Association (ERSA), 2010)
Firms locate in different areas for different reasons. However, some of them tend to move a new place in order to achieve alternative goals. For instance, the manufacturing survey in 2005 reflects that 30 per cent of the manufacturing firms in the Istanbul Metropolitan Area would like to relocate. Consistently, this paper considers two research questions: the first one is which factors do increase the probability of relocation tendencies of manufacturing firms? The second one is do factors that increase or decrease the probability of relocation tendencies change according to firm size and varying manufacturing sectors? Therefore, the aim of the study is to investigate what guides relocation decisions of manufacturing firms' according to firm size and varying sectors. Investigation is done by applying conditional logit model. In the first step, the reasons for relocation tendency are explored initially in relationship to the age of the firm, tenure, total employment and total capital. Added explanation then considers the physical conditions of production site: total size of the production site, age of the building and the type of the building. The analysis is expanded by adding location effects in the third step. Location effect of input transport cost, location effect of output transport cost and location effect of labor market is analyzed to demonstrate how they increase the likelihood of a firm relocation decision. Further, environmental characteristics are added to elaborate their impact on the probability of a firm relocation decision. It is expected that consistent variables would provide a significant source of explanation in any model.
Keywords: 330